Factors Related To Smoking Behavior In Papua Kamasan Ii Bandung Students In Cihapit District, Bandung Wetan District, Bandung City - Yani, Tri Ardayani (Journal of health research and technology, 2025)
Smoking is the process of burning tobacco to be lit, inhaled, and smoked, especially white cigarettes, kretek, cigars that come from plants. Smoke from burning tobacco contains tar and nicotine. It turns out that smoking behavior is not only limited to adults in Indonesian society, but also reaches teenagers. Generally, men and women start smoking when they enter adolescence. This research method is quantitative research with a cross-sectional study design. The population of this study was 200 respondents. The sample in this study was selected through a proportionate random sampling technique, namely 80 respondents. The dependent variable is smoking behavior and the independent variables are knowledge, attitudes, peers, cigarette advertising and the ability to buy cigarettes. Results Knowledge has a relationship (p value = 0.000), attitudes have a relationship (p value = 0.000), peers have no relationship (p value = 0.304) and cigarette advertising has no relationship (p value = 0.230) Conclusion there is a relationship between Knowledge, attitudes, and peers, cigarette advertising has no relationship. Suggestion Because there are some that have a relationship and some that do not have a relationship, it is important to provide information that smoking is not allowed in rooms, public places and smoke-free friends and it is also important to make preventive efforts about the dangers of cigarettes to Papuan students, friends II Bandung